Microsoft Project beginners 2016 (Packt Publishing, 2019)
"MS Project helps you develop a plan, assign resources to tasks, track progress, manage your budget, and analyze workloads. This video course, taught by a professional trainer with a background in project management, takes you, step-by-step from the very beginning, through all these functions. You'll go from very simple projects to a more complete knowledge of Project's capabilities and how it works. This course starts right at the very beginning. It doesn't assume you know anything about Microsoft Project, so beginners will feel right at home. You'll learn how to get your own copy of Project 2016, see what's new in version 2016, and explore the structure of this course. The second chapter supplies the basics you need to begin using Project 2016. It first discusses the Help section, where you can get answers and tutorials for any question that comes up. This chapter also discusses creating a workspace, using toolbars, ribbons, and the Status Bar. You'll go on to learn how to use Touch, task basics and project options. By now, you will have become proficient with Project 2016. These more advanced topics carry you through tracking costs, tracking projects, budgeting, and reporting. Upon completion of the course, you'll have mastered Microsoft Project 2016"--Resource description page